Clinical and experimental parallels in the substantiation of the method of hernioplasty of postoperative ventral hernias of median localization - V. L. Korobka; V. K. Tatyanchenko; R. O. Dabliz; S. V. Tolstopyatov; M. V. Gonchar; I. S. Kletz (Медицинский вестник Юга России, 2024)
Objective: development, clinical application of a new original method of hernioplasty of median postoperative ventral hernias and biomechanical experimental substantiation of the effectiveness of this method.Materials and methods: the method of hernioplasty of median postoperative ventral hernias with strengthening of fascial-aponeurotic structures of the anterior abdominal wall was developed and clinically tested on 63 patients. An anatomical experiment was performed in which the biomechanical parameters of the reinforced scar-altered structures of the median parts of the anterior abdominal wall were studied according to the method developed by us.Results: an increase in the biomechanical parameters of the median structures reinforced by the original method with a frame thread was found: the strength limit of the fascia — by 59.4%, and the modulus of elasticity — by 40.2%, compared with the scar-altered fascia in herniators. These results suggest a confident prevention of recurrence of herniation when using this technique. This assumption was confirmed after the introduction of the technique into clinical practice. In all 63 observed patients, there is no recurrence of herniation for 1-5 years. There were no significant complications of the course of the early postoperative period associated with the applied method of plastic surgery. The method is characterized by material and financial accessibility, the absence of complex technical manipulations that increase the duration of hernioplasty.Conclusions: the effectiveness in preventing recurrence of herniation, accessibility and simplicity of the proposed method of surgical treatment of postoperative and recurrent ventral hernias allows us to recommend it for wide clinical use.